Determinants of Chronic Energy Deficiency (CED) among Pregnant Women - Aswar, Sophian; Istyanto, Febry (GLOBAL HEALTH SCIENCE GROUP, 2024)
Maternal health is a crucial global development issue, particularly in developing countries like Indonesia. The health of pregnant women is vital for ensuring the survival and well-being of their unborn children. This study aims to identify factors contributing to Chronic Energy Deficiency (CED) in pregnant women and its effects on maternal health and fetal development. Conducted as an analytical survey with a cross-sectional design, the study's population comprises all pregnant women in their first, second, and third trimesters within the Yendidori Health Center area, totaling 63 individuals. Using a non-probability sampling method with incidental sampling, a sample of 45 participants was selected. Data collection involved observation sheets and a validated questionnaire on maternal knowledge, demonstrating high reliability (Cronbach's alpha = 0.951). Bivariate analysis revealed significant relationships between several factors and CED incidence: education level (p = 0.004), family income (p = 0.002), and nutritional knowledge (p = 0.001). These findings indicate that higher educational attainment, increased family income, and better nutritional knowledge are associated with a lower incidence of CED among pregnant women, highlighting the need for targeted interventions to improve maternal health outcomes.